FEATURES OF CULTURAL AND LANGUAGE ADAPTATION OF RUSSIAN EXPATRIATES: THE PAST AND THE PRESENT - E. V. Evpak (Вестник Кемеровского государственного университета, 2016)
The paper focuses on the problems of cultural and language adaptation of Russian expatriates abroad. It reflects a certain stage of an extensive research project carried out by the “Social-Cognitive Functioning of the Russian Language” school lead by N. D. Golev. The paper verifies the author’s observations about the cultural and linguistic adaptation of Russian expatriates in foreign countries in different historical periods. It is based on the evidence gathered by the author in the countries of the Russian Diaspora, as well as on archive materials, including the family and library archives in Russia, Slovakia and the Czech Republic.